Keterlaksanaan Model Pembelajaran Kooperatif Tipe Round Robin Brainstorming Pada Siswa Kelas V UPT SPF SD Inpres Kassi-Kassi 1 Kota Makassar - Suci Damayanti; Yusuf, Faidah; Syamsuddin, Afdhal Fatawuri (ETEDU : Elementary of Teacher Education, 2024)
This research was motivated by the lack of effective learning models to improve the speaking skills of Grade V students at UPT SPF SD Inpres Kassi-Kassi 1 in Makassar. The aim of this study was to describe the implementation of the cooperative learning model, Round Robin Brainstorming, among Grade V students. The research used a quantitative approach with a quasi-experimental design, specifically the nonequivalent control group design. The study involved two classes: the experimental class (VA) and the control class (VB), selected through purposive sampling. Data was collected using observation sheets. The results showed that the implementation of the Round Robin Brainstorming model was highly successful, with the implementation percentage increasing from 83% to 95%. This model proved to be effective in improving students' speaking skills in the Indonesian language subject.